The Dimensions of the Structure of MSM with HIV toward the Prevention of HIV and AIDS Transmission: A Qualitative Study - M. Nur Khamid; Eti Poncorini Pamungkasari; Argyo Demartoto; Dewi Rokhmah (Universitas Muhammadiyah Jember, 2022)
Men who have sex with men (MSM) are the most vulnerable key population in the transmission of HIV AIDS. They have closed behavior that makes it difficult for health programs to reach. This study explores the structural dimensions of MSM with HIV in preventing HIV AIDS transmission from the perspective of social networks and associations among MSM with HIV. This qualitative study with a grounded theory approach was conducted in Jember. Data were collected by using in-depth interviews with 12 HIV-positive MSM. Data were analyzed with the stages of codes, categorizing, and basic social-psychological processes. The triangulation is used to obtain the validity of the information. Being an MSM group for a long time, related to social networks and associations. The social network perspective is built through gathering activities with fellow MSM communities, gathering in cafes, boarding houses, own homes, rented houses, town square, and night entertainment places. Providing health information, safe sex, asking for HIV tests, and monitoring ARV is more manageable through the same HIV-positive MSM. The involvement of HIV-positive MSM in social activities or other environments can reduce the stigma and discrimination. From the association's perspective, to facilitate the socialization of HIV AIDS prevention are carried out through social activities. A few HIV-positive MSM use herbal medicine and do not believe in ARV. Regular peer group support activities can provide a correct understanding of the importance of ARV to minimize the risk of loss to follow-up. Elements of social networks and associations through peer group supports involved in social activities can facilitate communication, information, and education; also, controlling sexual behavior prevents HIV AIDS transmission. The policymakers need to strengthen community-based associations.